Does miscarriage in an initial pregnancy lead to adverse obstetric and perinatal outcomes in the next continuing pregnancy? - Bhattacharya, S; Townend, J; Shetty, A; Campbell, D; Bhattacharya, S (2008)
OBJECTIVE: To explore pregnancy outcomes in women following an initial miscarriage. DESIGN: Retrospective Cohort Study. SETTING: Aberdeen Maternity Hospital, Aberdeen, Scotland. POPULATION: All women living in the Grampian region of Scotland with a pregnancy recorded in the Aberdeen Maternity and Neonatal Databank between 1986 and 2000. MAIN OUTCOME MEASURES: (A) Maternal outcomes: Pre-eclampsia, antepartum haemorrhage, threatened miscarriage, malpresenation, induced labour, instrumental delivery, Caesarean delivery, postpartum haemorrhage and manual removal of placenta. (B) Perinatal outcomes: preterm delivery, low birth weight, stillbirth, neonatal death, Apgar score at 5 minutes. METHODS: Retrospective cohort study comparing women with a first pregnancy miscarriage with (a) women with one previous successful pregnancy and (b) primigravid women. Data were extracted on perinatal outcomes in all women from the Aberdeen Maternity and Neonatal Databank between 1986 and 2000. RESULTS: We identified 1561 women who had a first miscarriage (1404 in the first trimester and 157 in the second trimester), 10 549 who had had a previous live birth (group A) and 21 118 primigravidae (group B). The miscarriage group faced a higher risk of pre-eclampsia (adj OR 3.3, 99% CI 2.6-4.6), threatened miscarriage (adj OR 1.7, 99% CI 1.5-2.0), induced labour (adj OR 2.2, 99% CI 1.9-2.5), instrumental delivery (adj OR 5.9, 99% CI 5.0-6.9), preterm delivery (adj OR 2.1, 99% CI 1.6-2.8) and low birthweight (adj OR 1.6, 99% CI 1.3-2.1) than group A. They were more likely to have threatened miscarriage (adj OR 1.5, 99% CI 1.4-1.7), induced labour (adj OR 1.3, 99% CI 1.2-1.5), postpartum haemorrhage (adj OR 1.4, 99% CI 1.2-1.6) and preterm delivery (adj OR 1.5, 99% CI 1.2-1.8) than group B. CONCLUSION: An initial miscarriage is associated with a higher risk of obstetric complications.